Performer’s Rights Under the Copyright Law - Trika, Akash; Pattnaik, Annapurna (International Journal of Psychosocial Rehabilitation, 2025)
The research paper aims to elucidate the performer’s rights as a part of the copyright law regime and its development over time. The paper talks about the neighboring rights that led to the emergence of performers’ rights before discussing the performer’s rights laid down in various international conventions. The rights relating to performers as they exist under the Indian Copyright Act, 1957 have also been discussed. The paper concludes by talking about the Indian judgements relating to the rights and throws light on the need for a regime that would grant better protection to the performers.